Генеза поняття «Автономне навчання» - Іжко, Євгенія Станіславівна (Національний університет біоресурсів і природокористування України, 2013)
UK: Стаття присвячена проблемі генези концепції навчання автономії. У статті висвітлюються зміни у філософії освіти, теорії навчання мови, політичних переконань і вказується на необхідність адаптації до швидких змін у технології. Визначені фактори, що пояснюють виникнення інтересу до автономії у сфері освіти. Підкреслюється важливість афективних, соціальних і психологічних факторів у вивченні мови. У статті робиться висновок, що автономне навчання тісно повязане з іншими стратегіями навчання.

EN: The article is devoted to the problem of the genesis of the autonomy learning concept. The aim of the paper is a retrospective analysis of the concept of "autonomy learning", its development and formation. The article highlights the changes in the philosophy of education, language learning theory, political beliefs and points to the need to adapt to rapid changes in the technology, communications and employment and to recognize that the ability to learn is more important nowadays than knowledge. The factors that explain the emergence of interest in autonomy in education were defined. The article emphasizes importance of affective, social and psychological factors in the acquisition of language. The recognition of these factors leads perception of the student as a central agent in the learning process and the recognition that this approach can contribute to a more effective and efficient learning. The article sums up that learning autonomy is closely linked to learning strategies. It was found out that Learning Strategies gradually become an important and integral part of the requirement of autonomous learning. The works of many scientists in autonomy learning were studied and analyzed. Some definitions of the concept “autonomy learning” were introduced in the table.
Генезис понятия «Автономное обучение»
The Genesis of the Concept of "independent Learning"
Keywords: автономія; розвиток; визначення факторів; підстави; стратегії; відповідальність; самостійність; autonomy; development; definition; factors; grounds; strategy; responsibility; independence; КФП